The effect of coping intervention on maternal competency in caring for premature infants at home - Rinik Eko Kapti; Yuni Sufyanti Arief; Mira Triharini; Qori 'ila Saidah; Ari Damayanti Wahyuningrum (PAGEPress Publications, 2023)
The mother's ability to care for premature infants will affect the success of the interaction between mother and baby as well as the growth and development of the baby. The study aimed to assess the impact of coping interventions on mothers' ability to care for premature infants at home. This quasi-experimental research involved 80 respondents, divided into a treatment group and a control group, with 40 participants in each. The treatment group received a 3-month coping intervention, while the control group did not. The mothers' abilities were evaluated using questionnaires and the Developmental Pre-Screening Questionnaire (KPSP) instrument. The results revealed significant improvements in the treatment group's abilities in providing nutrition, maintaining body temperature, preventing infection, recognizing danger signs, and stimulating development in premature infants. These positive outcomes underscore the effectiveness of coping interventions in enhancing maternal abilities. It is recommended that health workers incorporate coping interventions into their support for mothers of premature infants, aiming to empower them with the skills and knowledge needed for better care and development of their infants at home. This approach can contribute to the overall well-being and growth of premature infants while reducing the burdens on healthcare providers.